Blood Profile and Histology in Oral Infections Associated with Diabetes - Cintra, Luciano Tavares Angelo [UNESP]; Silva Facundo, Aguinaldo Candido da [UNESP]; Carrara Prieto, Annelise Katrine [UNESP]; Sumida, Doris Hissako [UNESP]; Narciso, Luis Gustavo [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Oliveira e Silva, Cleverson; Dezan Junior, Eloi [UNESP]; Gomes Filho, João Eduardo [UNESP] (Elsevier B.V., 2014)
Introduction: We aimed to investigate the relationship between blood profile and histologic findings in both apical periodontitis (AP) and periodontal disease (PD) associated with diabetes. Methods: Wistar rats (N = 80) were assigned to the following 8 groups: control, AP, PD, AP associated with PD, diabetes, diabetes with AP, diabetes with PD, and diabetes with AP and PD. Diabetes mellitus (DM) was induced with streptozotocin, AP was induced by exposure to the oral environment, and PD was induced using periodontal ligature. After 30 days, blood samples were collected, and the rats were euthanized. Subsequently, the maxillae were processed for light microscopy. Hematologic examinations were conducted to determine the total number of erythrocytes and leukocytes, erythrocyte constant, and blood glucose level. One-way analysis of variance and Kruskal-Wallis tests were used for statistical analysis, and the significance was set at P < .05. Results: A significant correlation was found between the histologic findings and blood parameters. Conclusions: In conclusion, diabetes accelerated the development and progression of AP and PD in the rats and caused an increase in the average erythrocyte volume as well as the leukocyte and neutrophil counts. Oral infections increase the total number of leukocytes, the number of neutrophils and lymphocytes, and blood glucose concentrations in DM rats.
Keywords: Apical periodontitis; blood count; diabetes; oral infections; periodontal disease